Community acceptance of available milk and assessment of its quality in peri-urban area of Southwest Delhi - Purnima Rai; Sumant Swain; Pankaj Talreja (Wolters Kluwer Medknow Publications, 2020)
Background: Milk is considered to be a balanced food rich in fats, proteins, vitamins, and minerals, which is complete nutrition in a balanced proportion. However, most of milk sold in India does not match standards laid down by the Food Safety and Standards Authority of India. Objective: The objective was to understand the perception of community regarding the acceptance of packaged and unpackaged milk, to assess the quality of milk with respect to adulterants, and to assess the difference in the quality of milk at a level of vendor/hawker and end user. Materials and Methods: A cross-sectional study was conducted among 100 households in the peri-urban area of Kangan Heri, Delhi. A structured questionnaire and checklist were used for data collection. Purposive sampling was used. The analysis was done with the Statistical Package for the Social Sciences version 22. Descriptive statistics and cross tabulation were used. Results: A total of 22.5% respondents preferred packaged milk over unpackaged milk. Only 8% of packaged milk samples contained no adulterant. Majority of the respondents were preferred unpacked milk for daily consumption. Conclusion: Community perceives good taste as traits of good quality milk followed by good smell, digestibility, and color and economical. The presence of neutralizer in packaged milk followed by detergent and urea. There was no difference in the presence of adulterants in packaged milk at the level of end user or vendor. There is a slight difference in the presence of adulterants in unpackaged milk at level of end user.